The convergence of welfare state indicators in Europe: evidence from panel data - Paetzold, Jörg (Salzburg, 2012)
"This paper investigates whether there is a convergence in welfare state policies among the old EU member states. To identify such trends, we rely on pension and unemployment net replacement rates as well as on public social expenditures. Empirically, we use a sample of 14 economies (EU-15 excl. Lux.) between 1980 and 2005. The empirical findings reveal a presence of a convergence process, driven by strong catch-up of social protection levels in the Southern member states. Furthermore, convergence in replacement rates is substantially less pronounced than using spending data."